Cytochrome P450 aromatase (CYP19) gene expression in ovarian granulose cells of hypothyroid rats induced by propylthiouracil - Prihatin Broto Sukandar; Sri Kadarsih Soejono; Totok Utoro (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2013)
Thyroid hormones are proven to have a direct effect on granulose cells, luteal cells and oocytesdue to their role in gonadotropin action on steroid hormone production. In vitro study showedthat tiroxine (T4) on granulose cells can stimulate ovarian steroidogenesis. Moreover, highconcentration of triiodothyronine (T3) increases the estradiol secretion and aromatase mRNAexpression. Hypothyroidism influences the cytochrome P450 aromatase (CYP19) gene expression.The aim of this study was to evaluate the expression of the CYP19 gene in granulosa cells ofhypothyroid rats induced by propylthiouracil (PTU). This was quasi experimental study withpost-test only control group design. Eleven female Sprague-Dawley rats were divided into twogroups i.e. five rats as treated group that induced by PTU 0.1 g/L in aquadest for 30 days andcontrol group that not induced by PTU. Blood sample was taken and then T4 blood level wasmeasured using an enzyme-linked immunosorbent assay (ELISA). Whereas, CYP19 gene expressionin ovarian granulose cells was measured using immunohistochemistry. Unpaired t test was usedto compare the data obtained from treated and control groups. The results showed that T4blood level on treated group (4.02 ± 0.39 ng/dL) was significantly lower than control group(8.08 ± 1.63 ng/dL) (p = 0.000). However, CYP19 gene expression on treated group (30.84 ±8.01%) was not significantly different compare to control group (25.06 ± 6.79%) (p = 0.227).In conclusion, the CYP19 gene expression in ovarian granulose cells of rats is not change afterinduction of PTU 0.1 g/L for 30 days, although the T4 blood level decreases.